Poor Management of Scabies Among Female Residential Madrasa Students of Bangladesh Caused by Poor Hygiene (The Journal of Ad-din Women's Medical College, 2025)
Abstract not availableThe Journal of Ad-din Women's Medical College; Vol. 12 (2), July 2024; p 30-31